Witches : true encounters with wicca, wizards, covens, cults, and magick - Holzer, Hans, 1920- (New York : Black Dog & Leventhal, 2002)
A wide-ranging exploration of witchcraft, from druidism to the many cults practicing today, featuring documents, interviews, spells, rituals, eyewitness accounts and photographs. This book is available in large page size and wide spine width and it contains 200 photographs, including "insider" photos of secret rituals.
Keywords: Witchcraft